Development Of ICT Instructional Materials Based On Needs Identified By Malaysia Secondary School Teachers. - Ngah, Nor Azilah; Masood, Mona (2006)
For the last few years school teachers in Malaysia have access to ICT tools in their schools. However,these tools are used mostly for record keeping and word processing purposes.